Outcome of Pediatric Large Vessel Occlusion Stroke in Denmark - Julie Brix Bindslev; Klaus Hansen; Nicol Dara Matoor; Trine Stavngaard; Christina Engel Hoei‐Hansen; Thomas Truelsen (Stroke: Vascular and Interventional Neurology)
Background We performed a nationwide study to examine clinical outcome in children with large‐vessel occlusion (LVO) stroke treated with mechanical thrombectomy (MT) or conservatively. Methods Study participants were enrolled by 2 methods: (1) registration of children assessed through a pediatric stroke triage‐setup from January 2021 to June 2023 and (2) identification of children registered with a stroke or stroke‐related diagnosis in the Danish National Registry of Patients between January 2011 and December 2020. Medical records were reviewed to validate possible stroke events. Children aged 29 days to 17 years with arterial ischemic stroke were included. The children were followed up for cause of stroke, site of vessel occlusion, treatment characteristics, and clinical outcome according to the modified Rankin scale. Results A total of 181 children with arterial ischemic stroke were identified. Angiography descriptions were available in 133 children and demonstrated LVOs in 28 (21.1%) of these. Fourteen children with LVOs underwent MT and 14 were treated conservatively. Thirteen of 14 (92.9%) children treated with MT achieved successful reperfusion. Periprocedural complications were observed in 2 children, including 1 child who developed symptomatic intracerebral hemorrhage <24 hours from MT. Long‐term outcome was poor (modified Rankin scale score 3–6) in 7 out of 14 (50.0%) children with LVOs treated conservatively and 5 out of 14 (35.7%) children treated with MT. When limiting analysis to MT procedures performed within 24 hours from stroke onset, a poor outcome was observed in 3 out of 11 (27.3%) children treated with MT. Outcome did not differ significantly between treatment groups. Conclusion This nationwide study demonstrates that MT is feasible and apparently safe to use in children. Among children with LVOs, outcome tended to be better for those treated with MT than those treated conservatively, but outcome did not differ significantly between groups, likely due to small sample sizes.